Correlation between dietary factors and Parkinson’s disease revealed by the analysis of Mendelian randomization - Zeng, Shan; Yusufujiang, Aishanjiang; Zhang, Chunli; Yang, Chen; Li, Hongyan (Frontiers in Nutrition, 2024)
Background The intricate interplay between dietary habits and the development of Parkinson’s Disease (PD) has long been a subject of scientific inquiry. Mendelian Randomization (MR) emerges as a potent tool, harnessing genetic variants to infer causality in observational data. While evidence links diet to Parkinson’s Disease (PD) etiology, a thorough MR exploration of dietary impacts on PD, particularly involving gut microbiota, is still emerging. Methods This research leverages the IEU Open GWAS project’s vast GWAS database1 to address the knowledge gap in understanding diet’s influence on PD, employing a diverse range of dietary variables. Our holistic dataset includes various foods like processed fava beans, bap, red wine, to cheese, reflecting a commitment to untangling dietary complexities in PD etiology. Advancing from initial dietary-PD associations, we innovatively explore the gut microbiota, focusing on Parabacteroides goldsteinii, in relation to bap intake and PD, employing MR. Utilizing weighted median, MR-Egger, and inverse variance weighting methods, we ensure rigorous causality assessments, meticulously mitigating pleiotropy and heterogeneity biases to uphold finding validity. Results Our findings indicate red wine (OR: 1.031; 95% CI 1.001–1.062; p = 0.044) and dried fruit consumption (OR: 2.019; 95% CI 1.052–3.875; p = 0.035) correlate with increased PD risk, whereas broad beans (OR: 0.967; 95% CI 0.939–0.996; p = 0.024) and bap intake (OR: 0.922; 95% CI 0.860–0.989; p = 0.023) show protective effects against PD. Employing MR, specifically the IVW method, revealed a significant inverse association between bap intake and gut microbiota, marked by an 8.010-fold decrease in Parabacteroides goldsteinii per standard deviation increase in bap intake (95% CI 1.005–63.818, p = 0.049). Furthermore, a connection between PD and Parabacteroides goldsteinii was observed (OR: 0.810; 95% CI 0.768–0.999; p = 0.049), suggesting a potential microbiota-mediated pathway in PD etiology. Conclusion Our study links dietary habits to PD risk, showing higher PD risk with red wine and dried fruit consumption, and a protective effect from broad beans and bap. Using MR, we found bap intake inversely correlates with Parabacteroides goldsteinii in the gut, suggesting bap influences microbiota. Further, higher Parabacteroides goldsteinii levels correlate with lower PD risk, highlighting a complex interplay of diet, gut microbiome, and neurological health. These insights shed light on potential dietary interventions for PD.